Random time source protocol in wireless sensor networks and synchronization in industrial environments. Issue 8 (17th May 2011) - Wang, Fuqiang; Zeng, Peng; Yu, Haibin; Xiao, Yang
ABSTRACT Reliability is a crucial aspect of time synchronization for industrial wireless applications in wireless sensor networks. Existing time synchronization algorithms often provide good synchronization in laboratory environments; however, outdoor environments with associated radio interference influence the performance of time synchronization. In this paper, we propose a random time source protocol for industrial wireless applications in wireless sensor network synchronization. Each synchronized node randomly selects its time source for each period in order to prevent reliance on a fixed time source because this may lead to resynchronization once the source fails. We have implemented the algorithm on the SIA2420 platform using TinyOS, and the results show the reliability of our protocol. Copyright © 2011 John Wiley & Sons, Ltd.